2019
DOI: 10.3389/fphys.2019.01025
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Pacific White Shrimp Litopenaeus vannamei to Temperature Fluctuation in Low-Salinity Water

Abstract: Temperature is a significant environmental factor in aquaculture. To investigate the physiological responses during temperature fluctuation (28~13°C), experimental shrimps ( Litopenaeus vannamei ) were treated with gradual cooling from acclimation temperature (AT, 28°C) to 13°C with a cooling rate of 7.5°C/day and rose back to 28°C at the same rate after 13°C for 24 h. Hepatopancreas histological changes, plasma metabolites concentrations, relative mRNA expression of unfolded protein res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 54 publications
3
10
0
3
Order By: Relevance
“…When the water temperature changes beyond the tolerance temperature range of poikilothermic animals, oxygen free radicals increase, antioxidant-enzyme activity decreases, oxidative damage is aggravated, and immunity becomes suppressed in the organism [ 3 , 4 ]. To adapt to the drastic changes in the surrounding environment, individuals have evolved a series of temperature stress response mechanisms, such as unfolded-protein response and apoptosis [ 5 ], activation of desaturases [ 6 , 7 ], and increased lipid metabolism [ 8 ]. In addition, as a class of molecular chaperones, heat shock proteins can prevent protein denaturation and play a critical role in an organism’s resistance to environmental stress [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the water temperature changes beyond the tolerance temperature range of poikilothermic animals, oxygen free radicals increase, antioxidant-enzyme activity decreases, oxidative damage is aggravated, and immunity becomes suppressed in the organism [ 3 , 4 ]. To adapt to the drastic changes in the surrounding environment, individuals have evolved a series of temperature stress response mechanisms, such as unfolded-protein response and apoptosis [ 5 ], activation of desaturases [ 6 , 7 ], and increased lipid metabolism [ 8 ]. In addition, as a class of molecular chaperones, heat shock proteins can prevent protein denaturation and play a critical role in an organism’s resistance to environmental stress [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that glucose was significantly increasingly consumed after cold stress. Similarly, plasma glucose levels in pacific white shrimp ( Wang et al, 2019 ) and mucus glucose in gilthead sea bream ( Sanahuja et al, 2019 ) were also reduced in response to cold stress. On the gene level, we found the carbohydrate metabolism activity was decreased since the starch and sucrose metabolism, as well as the glyoxylate and dicarboxylate metabolism, were significantly downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the activities of AST, ALT and ALP increased at 12 h after LPS injection while the histological changes in the hepatopancreas were first found at the same time. Our previous study showed that cold stress caused hepatopancreas damage and ERS, which activated UPR pathway and accelerated the apoptosis process (Wang, Qu, Yan, et al, 2019; Wang et al, 2019). Therefore, we speculated that LPS injection might cause ERS and even accelerated the apoptosis process.…”
Section: Discussionmentioning
confidence: 99%